Effect of physical activity on cognitive function and sleep quality among UiTM Seremban 3 students / Akif Saat ... [et al.]. - Saat, Akif; Naja, Nurun; Najihah, Nur; Sahira, Naimi; Taufiq, Muhammad; Syed Mud Puad, Sharifah Maimunah (2024)
In the demanding landscape of university life, where sleep deprivation and mental exhaustion are commonplace, this study explores whether physical activity could be a game-changer for students, enhancing both academic success and overall well-being. Could physical activity be key to unlocking more significant cognitive potential and ensuring restorative sleep? Purpose: Although exercise and sleep quality are associated with cognitive function, their beneficial effects on cognitive function remain unclear. This study examines the impact of physical activity on sleep quality and cognitive function. Methods: 26 healthy young adults (age 22.3 ± 1.04 years) participated in this study. The Exercise amount was assessed using a uniaxial accelerometer. This study evaluated physical activity and sleep quality by actigraphy. Cognitive function was tested using the N-back task and the Wisconsin Card Sorting Test (WCST).Results: There were no significant associations between physical activity and sleep quality (B = -2.63e-4, p = 0.616), Nback task performance (B = -2.84e-4, p = 0.670), or WCST performance (B = -2.61e-5, p = 0.679), while sleep quality was significantly associated with N-back task performance (B = 0.540, p = 0.030) but not WCST performance (B = 0.0401, p = 0.097). Conclusion: Physical activity was not significantly associated with sleep quality or cognitive function. However, sleep quality was positively associated with working memory performance, suggesting that better sleep quality may enhance cognitive abilities in specific domains.